ORGANIZATIONAL AND ECONOMIC MEASURES TO INCREASE THE EFFICIENCY OF THE PROCESS OF THE FORMATION OF PERSONNEL OF INDUSTRIAL ENTERPRISES - Prydatko , E.М. (The actual problems of regional economy development, 2018)
The article is devoted to the substantiation of organizational and economic measures, the introduction of which at the level of an industrial enterprise should allow to increase the efficiency of personnel formation processes. The object of research are processes of forming the personnel of industrial enterprises of Ukraine. In substantiating the organizational and economic measures, the methods of grouping, logical generalization and systematization were used. The presence of two groups of factors affecting the degree of efficiency of baking of the processes of forming the personnel of industrial enterprises – internal and external. Five main factors are identified in each group, which have the greatest impact on the research object. The main organizational and economic measures are proposed to prevent the possible negative impact of each of the factors.